Health-based network node importance assessment - Jianwei LIU; Bin JIANG; Pu YANG (物联网学报)
For the identification of key nodes in network systems, a node importance assessment method based on the system health state was proposed.Firstly, the definition of the system health degree was analyzed.Then, according to the connection relationship between network nodes, the adjacency matrix was established to calculate the network capacity change under normal conditions and fault degradation conditons.And the relationship model between the system health degree and the node importance degree was established.Finally, simulations of network systems showed that this method could effectively identify the key nodes in the system and improve the reliability of the network.